The effect of parental enhancing program with mobile application on parental stress and competence among Thai adolescent postpartum women: A quasi-experimental matched control design - Sunee Kleebpan; Pornpimol Apartsakun; Pensiri Chaiyanusak; Ellen Kitson-Reynolds (PLoS ONE, 2025)
Background Adolescent pregnancy constitutes a critical public health issue worldwide. Young mothers face substantial physical and psychological changes as they transition to motherhood, while limited knowledge, experience, and maturity may impair parenting and increase stress. The study aimed to evaluate the effects of the parental enhancing program with mobile application on parental stress and competence among Thai adolescent postpartum women. Methods A quasi-experimental study using a matched control design was conducted among sixty adolescent postpartum women, aged 15−19. Participants were sequentially allocated to an intervention group (n = 30) receiving a parental enhancing program with mobile application, and a control group (n = 30) receiving standard postpartum care. Adolescent postpartum women in the intervention group received two sessions from the parental enhancing program before discharge with weekly follow-up through the Line Official Account™. Data were collected using questionnaires, including the Edinburgh Postnatal Depression Scale (EPDS), Parenting Stress Index (PSI-4-SF), and Parenting Sense of Competence Scale (PSOC). Evaluations were conducted during the 6-week postpartum. ANCOVA was used to compare post-intervention mean scores of parental stress and competence between groups. Results All enrolled participants completed the study (Intervention: 30; Control: 30). At 6-weeks postpartum, after controlling baseline EPDS scores, the results revealed that adolescent postpartum women in the intervention group demonstrated significantly lower parental stress (F(1,57) = 14.40, partial η² = 0.20, 95% CI [−14.05, −4.34], p < .001) and higher parental competence (F(1,57) = 8.79, partial η² = 0.13, 95% CI [1.90, 9.80], p < .01) compared to the control group. Conclusion The parental enhancing program with mobile application demonstrates promise for evidence of reducing parental stress and improving parental competence in postpartum adolescent mothers. However, further studies in randomized controlled trials are warranted to confirm its effectiveness and generalizability. Trial registration Thai clinical trials registry (TCTR20250309010).